P-129 Gimap5 Is Required for GSK3ß Inhibition Controlling the Transcriptional Program Required for T Cell Proliferation/Differentiation While Maintaining Gut Homeostasis. (March 2016) - Patterson, Andrew; Endale, Mehari; Lampe, Kristin; Woodgett, Jim; Hoebe, Kasper
Abstract : Background: Polymorphisms in human GIMAP5 have been associated with auto-immune/inflammatory diseases, while in mice loss of Gimap5 causes impaired T cell survival/proliferation and severe early onset CD4 + T cell dependent colitis. The latter was associated with an abnormal Treg/Th17 balance. Despite the important role of Gimap5 in T cell survival and peripheral tolerance, the underlying mechanism(s) have remained unclear. Using a forward genetics approach, we have identified a point mutant in Gimap5, so-called "sphinx" mice. Gimap5sph/sph mice have a missense mutation in Gimap5 that results in essentially a null allele. We found Gimap5-deficieny resulted in 2 major immunological effects. First, the sphinx mice progressively lose Treg function and are unable to induce Treg cells in vivo. Second, the mice progressively develop lymphopenia, a dramatic loss of Foxo expression, and the remaining CD4 + T cells all have an activated Th17 phenotype, but yet fail to undergo proliferation. These immunologic defects result in a spontaneous colitis that is preventable with either (1) CD4 + T cell depletion; (2) Treg transplant; (3) or antibiotic therapy. Despite these effective therapies, the cell-intrinsic defects in Gimap5sph/sph CD4 + T cells are not restored. Here we test the hypothesis that Gimap5 is required for inhibition of glycogen Synthase Kinase-3 (GSK3) following TCR-signaling. A reduced inhibition of GSK3-activity causes an impaired transcription factor (TF) program unable to support T cell proliferation and iTreg development ultimately causing severe early onset gut inflammation. Methods: Studies involve flow cytometric/Imagestream analysis of isolated WT or Gimap5sph/sph mice; Cd4-cre/ERT2; GSK3βfl/fl mice and therapeutic targeting of GSK3 by using LiCl or 6-bromoindirubin-3'-oxime both in vitro and in vivo. Results: Genetic or therapeutic targeting of GSK3 in Gimap5-deficient mice recovered T cell proliferation in vitro and resulted in normal survival of CD4 + T cells in vivo. Moreover, while Gimap5-deficient T cells exhibit a reduced expression of c-Myc and Foxo, GSK3 inhibitors completely restored the expression of these TFs. Importantly, genetic/chemical targeting of GSK3β in vivo completely prevented gut pathology and improved lymphocyte survival in Gimap5-deficient mice. Further imagestream analyses suggest Gimap5 to control inhibition of GSK3 through a unique mechanism involving sequestration of GSK3 in multivesicular bodies and lysosomes. Conclusions: Our studies uncover a novel regulatory pathway required for T cell activation and establish Gimap5 as an essential negative regulator of GSK3 activity controlling the TF program required for CD4 + T cell proliferation/differentiation. The uncovered pathway is critical for maintaining peripheral tolerance in the gut.